Chemical analyses of two plant essential oils and their effects on functional response of Habrobracon hebetor Say to Sitotroga cerealella Olivier larvae - Heidarian, Mehdi; Masoumi, Seyed-Mohammad; Asadi, Mohammad (Acta Biologica Szegediensis, 2022)
Salvia officinalis L. and Glycyrrhiza glabra L. are two valuable medicinal plants from Kermanshah province in Iran. In this study, chemical analyses of their essential oils were performed by gas chromatography-mass spectrometry and the effects investigated on functional response of Habrobracon hebetor Say on larval stage of Sitotroga cerealella Olivier. Accordingly, emerged females of H. hebetor were treated by LC30 of the isolated essential oils for 24 h. Then, six wasps were accidentally selected and introduced to densities of host larvae for 24 h. The results showed that naphthalene, decahydro-4a-methyl and alpha-thujone were dominant compounds in both essential oils, respectively. Holling model (1959) by using regression analyses confirmed functional response type III in the control wasps and type II in both essential oils treatments. The highest and lowest attack rates were observed in the control wasps (0.0443 ± 0.00278 h-1) and S. officinalis treatment (0.0349 ± 0.00257 h-1), respectively. Moreover, the treated wasps by G. glabra essential oil showed shorter handling time than S. officinalis treatment (0.4497 ± 0.0373 h versus 0.5196 ± 0.0589 h). Accordingly, G. glabra due to lower negative effects on the functional response of H. hebetor was more compatible than S. officinalis for their combination in integrated pest management schedules.